THE IMPACT OF ISLAMIC FINANCIAL INCLUSION ON INDONESIAN HUMAN DEVELOPMENT - Roni Mohamad; Rifadli D. Kadir; Chitra Yuliashri Katili; Nurul Fadhilah (Universitas Negeri Gorontalo, 2025)
This study seeks to examine the effect of Islamic financial inclusion on human development in Indonesia and to compare its effects between Western and Eastern Indonesia. The research included panel data from 33 provinces spanning the years 2018 to 2023, utilizing a quantitative methodology and a random effects regression model. The Islamic financial inclusion index is developed using the Principal Component Analysis (PCA) approach, including the dimensions of access, availability, and utilization of Islamic banking services. The study's findings indicate that Islamic financial inclusion positively and significantly impacts the Human Development Index (HDI) at both national and regional levels. The Western Indonesia region benefited most from IFI, but the Eastern region experienced a more uneven and lower impact. These results imply that more access to Islamic financial services can enhance people's standard of living, health, and education, all of which can impact their quality of life. The study advocates for the enhancement of Islamic financial infrastructure, the promotion of Islamic financial literacy, and the implementation of policies that address regional inequities.